HEXACO and Dark Triad predictors of psychological abuse in romantic relationships: forgiveness as a mediator - Taylor, Leanne (2020)
The HEXACO model of personality has seldom been used when researching intimate partner violence (IPV). We investigated whether HEXACO and Dark Triad (DT) traits predicted perpetration and victimisation of psychological IPV, and the reciprocity of the relationship between perpetration and victimisation. We also sought to determine whether forgiveness mediated the relationship between personality and perpetration/victimisation. Individuals aged 18-61 (n = 340) completed four questionnaires. Factor analysis revealed that Conscientiousness and Openness to experience did not load onto any factors, so were subsequently excluded from analysis. Bootstrapped multiple hierarchical regressions found that low Agreeableness and low eXtraversion predicted perpetration, but HEXACO traits failed to predict victimisation. DT traits did not predict victimisation or perpetration. The relationship between victimisation and perpetration was highly reciprocal as both variables strongly predicted the other. Resentment-avoidance was shown to partially mediate the relationship between significant predictors and psychological IPV. This research shows a cyclical relationship of psychological abuse, perpetuated by personality factors and the reciprocal relationship between perpetration and victimisation. It also suggests impulsive rather than instrumental aggression in the current cohort. Limitations and practical implications are discussed.